Comparison of cavity ring-down spectroscopy and Fourier transform infrared spectroscopy for the isotopic composition determination of CRMs of CO2 in air - Sega Michela; Durbiano Francesca; Pavarelli Stefano; Pennecchi Francesca Romana; Rolle Francesca (EPJ Web of Conferences)
Gaseous Certified Reference Materials (CRMs) characterised for the isotopic composition of carbon dioxide (CO2) in air at ambient amount fraction are crucial for understanding the anthropogenic contribution to climate change. At INRiM, the Italian National Metrology Institute, the realization of gaseous mixtures, which are candidate CRMs of CO2 in air at ambient level and known isotopic composition, is ongoing. Fourier transform infrared spectroscopy (FTIR) and cavity ring-down spectroscopy (CRDS) are used to verify the mixtures for their isotopic composition, in terms of δ13C-CO2 in the range from +1.3 ‰ VPDB to -42 ‰ VPDB. In this work, a comparison between the performances of the two analytical techniques FTIR and CRDS used at INRiM to assign the isotopic composition to the prepared candidate CRMs is presented.